The ups and downs of hipster cafes in Malaysia: navigating trends and challenges - Saidi, Normaizatul Akma; Mohd Radzi, Naziatul Aziah; Ahmad Raston, Nursalihah; Saidi, Noraida (Universiti Teknologi MARA, Terengganu, 2024)
In recent years, Malaysia has seen a burgeoning trend of hipster cafes, characterized by their unique aesthetics, artisanal coffee, and eclectic menus. These establishments have become popular spots for young urbanites and tourists alike, contributing to the vibrant cultural tapestry of Malaysian cities. However, the journey of these hipster cafes is not without its challenges. This article explores the rise of hipster cafes in Malaysia, the factors contributing to their success, and the obstacles they face in a dynamic and competitive market.